Cervical cancer analysis: From burden to treatment - Tiwari, Disha; Srivastava, Kirti; Kishan, Dewesh; Shah, Manjari (Asian Journal of Medical Sciences, 2018)
Background: Cancer has emerged as huge epidemic over past two decades. There is a declining trend in the incidence of cervical cancer in the western world on the contrary in India we have observed that this disease is a great menace to a women’s health and is showing rising trend. Within the country there is wide range of variation in demography and epidemiology. There is lack of published data available on epidemiology such as age, incidence, burden, compliance of patients having cervical cancer in Uttar Pradesh. Aims and Objectives: Current study aims to gather the evidence to understand the pattern of cervical cancer burden in the community and to find out the lacunae in the treatment delivery and receiving end. Materials and Methods: A retrospective study was conducted on patients of cancer cervix visiting OPD of department of radiation oncology. The study comprised retrieval of medical records for different variables like age, stage, district etc and analysing it to understand the presentation and burden of disease. Results: A total of 470 patients were studied for their epidemiology. Majority of patients were from Lucknow (78) and its nearby districts. Out of 75 districts of Uttar Pradesh, patients from 38 different districts had come to seek radiation treatment which is almost half of the Uttar Pradesh. Majority of patients in study were women in their 5th& 6th decade. The most common stage of diagnosis was II B. On histopathological evaluation most common variant found was squamous cell carcinoma with moderate differentiation 26.38%. Conclusion: Our study highlights lack of resources in Uttar Pradesh as patients had travelled from peripheral districts to seek treatment, which lead to frequent treatment breaks and poor compliance for follow up.